The Study Of The Antecedents Of Retail Shoppers' Repatronage Iintentions: A Empirical Study - Budi Hartono Kusuma; Andreas Widjaja (Jurnal Ekonomi, 2015)
One of the important factors that determine the success of retail stores is how to make customers go shopping there, in which they have to shop there continuously. So, retailers should have to satisfy customers in order to keep customers. In this research, the researcher would like to test and describe customer satisfaction and patronage intentions, through eights variables in Carrefour and Hypermart, and developed into seven hypotheses. This research uses 160 samples to ask their perceptions about Carrefour and Hypermart. Then, from that research, there are two hypotheses that are rejected and five hypotheses that are accepted. Perceived product quality and perceived price are considered as insignificant antecedents of customer satisfaction. However, perceived service quality, store assortment, trust and commitment are considered as significant antecedents of customers satisfaction, and customer satisfaction is a significant antecedent of patronage intentions.